2022
DOI: 10.1038/s41536-022-00227-6
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3 restricts liver regeneration by suppressing the proliferation of hepatocytes

Abstract: Upon injury, the liver is capable of substantial regeneration from the original tissue until an appropriate functional size. The underlying mechanisms controlling the liver regeneration processes are not well elucidated. Previous studies have proposed that the transcription factor FoxO3 is involved in various liver diseases, but its exact role in the regulation of liver regeneration remains largely unclear. To directly test the detailed role of FoxO3 in liver regeneration, both a constitutive Albumin-Cre drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…FOXO3 is associated with many age-related diseases, including cancer, cardiovascular disease, disc degeneration, and neurodegenerative diseases [ 29 ]. The research on the regulation of liver regeneration revealed that FOXO3 could limit liver regeneration by inhibiting hepatocyte proliferation [ 30 ]. Notably, FOXO3 was found to be enriched in the GO term of DNA damage response that exhibited significant enrichment in LCu.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3 is associated with many age-related diseases, including cancer, cardiovascular disease, disc degeneration, and neurodegenerative diseases [ 29 ]. The research on the regulation of liver regeneration revealed that FOXO3 could limit liver regeneration by inhibiting hepatocyte proliferation [ 30 ]. Notably, FOXO3 was found to be enriched in the GO term of DNA damage response that exhibited significant enrichment in LCu.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the deceased expression of FoxO3a is observed at the early stage of LR after PHx due to the direct transcriptional regulation by p53 and p73 [ 63 ]. A recent study reports that FoxO3a negatively controls hepatocyte proliferation and FoxO3a deletion accelerates LR [ 64 ]. Taken together, FoxO3a is a redox-sensitive transcription factor and a vital regulator of cell proliferation [ 21 , 23 ], making it the best candidate to bridge mitochondria-derived H 2 O 2 with LR after PHx.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our trained algorithm is an entirely automated, objective pipeline for the high-throughput processing of images. In addition to IF imaging, flow cytometry [ 14 , 21 , 27 , 28 , 29 ] and image cytometry [ 45 , 46 , 47 ] are frequently utilized in experimental research to accurately quantify ploidy. However, these methods have not seen widespread use in clinic because it is difficult to perfuse and obtain viable hepatocytes from biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the quantification of hepatic ploidy relies on two main technological approaches: flow cytometry and image-based analysis using immunofluorescence (IF) [ 12 , 15 , 16 , 17 , 18 , 19 , 25 , 26 ]. Flow cytometry [ 14 , 21 , 27 , 28 , 29 ] is the current gold standard for ploidy quantification. However, it requires fresh samples, which can be difficult to obtain in clinical settings.…”
Section: Introductionmentioning
confidence: 99%